Mapping the potential suitable habitats for Hyalomma rufipes (Acari: Ixodidae) in Africa and Western Eurasia. - Ruobing Zhou; Hein Sprong; Qiyong Liu; Thomas Krafft; Agustin Estrada-Peña (PLoS Neglected Tropical Diseases)
Crimean-Congo hemorrhagic fever is a broadly distributed tick-borne disease and is caused by the arthropod-borne Crimean-Congo hemorrhagic fever virus (CCHFV). Hyalomma ticks have been associated with the circulation of the virus in natural foci and in laboratory experiments. One of the main species, Hyalomma rufipes, is originally distributed in Africa. However, anthropogenic activities, bird migration, and domestic animal movement, could break the natural barriers that prevent its spread out of its natural area of colonization. This study explored the potential suitable areas for H. rufipes in Africa, Southern Europe and Central Asia using an environmental niche model. Explanatory variables based on climate were generated by harmonic regression of long-term climate; records of H. rufipes were obtained from public databases or provided by other scientists and researchers. The model indicated that areas likely to support permanent populations of H. rufipes are distributed across Southern Africa, Northern Africa, Southern Europe, the Arabian Peninsula, and the Caucasus. Data on migratory birds infested with H. rufipes further supports the need for surveillance activities in these regions to monitor and manage both the vectors and the pathogens they carry.